Monopolistic Competition and Preference Diversity - Deneckere, Raymond; Rothschild, Michael (Review of Economic Studies, 1992)
This paper presents a general model of the demand for differentiated products which has as special cases two popular models used to analyse welfare and competition in monopolistically competitive markets: the model of spatial competition and the symmetric aggregate benefit function approach. Our model is especially attractive because it starts from economic primitives: a specification of the set of possible individual preference patterns. It shows how specific properties of the distribution of preferences translate into properties of aggregate demand. This allows us to understand the relationship between the distribution of preferences and the degree to which the market introduces biases in product selection.